Improval of Water Quality in Aquapro - Sebastian, Preethi; Nainan, Susan V; Scaria, Jeneesh (International Journal of Computer Sciences and Engineering, 2025)
The current method of raising tilapia in the Philippines is through fish ponds exposed to the weather. Methods for measuring pH, temperature, dissolved oxygen, andammonia are limited to manually using a chemical test kit. The current system relies on manually regulating the water quality sothe fish are at risk of harmful situations resulting from unsafe levels of temperature, pH, dissolved oxygen, or ammonia. This study aims to solve that problem by creating a system that automatically measures and regulates the pH, temperature, dissolved oxygen, and ammonia. This study takes advantage ofelectronic sensors for pH, temperature, and dissolved oxygen, while computing the ammonia factor, to allow the user to measure the levels of the said parameters at any given time, process, send the data to a LabVIEW database, and use the datato automatically take corrective action against harmful levels ofpH, temperature, dissolved oxygen, and ammonia while notifyingthe user through SMS. The proponents of this study built theprototype and tested it on two different trials of 50 fingerlingseachina1cubic-meter glassaquarium.